Correlation between psychological factors, academic performance and social media addiction: model-based testing. Issue 8 (11th June 2022) - Malak, Malakeh Z.; Shuhaiber, Ahmed H.; Al-amer, Rasmieh M.; Abuadas, Mohammad H.; Aburoomi, Reham J.
ABSTRACT: Social media addiction became a serious concern that has received more attention from the public health sector due to its addictive features and its correlated psychological consequences. Thus, this study aimed to analyze the direct effect of SMA on academic performance, and the indirect effects on psychological reactions among university students in Jordan. A random survey in two universities was conducted in a sample of 510 university students; 31.4% were males and 68.6% were females. Their average age was 21.38 years (SD = 2.12). To test and validate the research model, advanced data analysis (Structural Equation Modelling-Partial Least Squares [SEM-PLS]) was applied in this research. Findings revealed that social media addiction had an indirect effect on academic performance, however; it has a direct impact on students' stress and anxiety levels. The stress could influence anxiety levels, which could directly affect students' academic performance. Further, students' stress levels had a direct effect on anxiety, which could result in depression. Given the importance of social media addiction and its potentially substantive effects on students' psychological reactions and impact of these reactions on academic performance, similar studies are recommended in other universities various fields to obtain a more conclusive result.